(untitled) (Моделювання, керування та інформаційні технології, 2023)
Navigation in military UAVs requires the use of onboard inertial systems. An approach is proposed for noise filtering, refinement of initial and intermediate values when applying calculation algorithms based on the estimates of loads and angular velocity taken from sensors.